144k views
5 votes
(3x +1)•2x – x^2 • 3
(3x + 1)^2

1 Answer

3 votes

Answer:

3x^2 +2x

9x^2 +6x+1

Explanation:


(3x +1)\cdot 2x - x^2 \cdot 3\\\\=2x\left(3x+1\right)-3x^2\\\\\mathrm{Expand}\:2x\left(3x+1\right):\quad 6x^2+2x\\\\=6x^2+2x-x^2\cdot \:3\\\\\mathrm{Simplify}\:6x^2+2x-x^2\cdot \:3:\\\quad 3x^2+2x

2.


(3x + 1)^2\\\\\mathrm{Apply\:Perfect\:Square\:Formula}:\\\quad \left(a+b\right)^2=a^2+2ab+b^2\\\\a=3x,\:\:b=1\\\\=\left(3x\right)^2+2\cdot \:3x\cdot \:1+1^2\\\\\mathrm{Simplify}\:\left(3x\right)^2+2\cdot \:3x\cdot \:1+1^2:\\\quad 9x^2+6x+1

User Rudd
by
5.6k points